Discoveries in indigenous territories: Two new species of Lepanthes (Orchidaceae: Pleurothallidinae) in southwestern Colombia - Moreno, Juan Sebastián; Pisso-Florez, Gustavo Adolfo; Vieira-Uribe, Sebastián (Lankesteriana: International Journal on Orchidology, 2020)
Two new species of Lepanthes from the Central Cordillera of the Colombian Andes are described and illustrated. Both were found during a botanical expedition to Puracé National Natural Park, within the high Andean forests ecosystem of the municipality of Puracé, in the department of Cauca. Key Words: Cauca, Colombian Massif, Kokonukos, Paletará, Puracé National Natural Park